Contribution of the Alternative Respiratory Pathway to PSII Photoprotection in C3 and C4 Plants - Zhang, Zi-Shan; Liu, Mei-Jun; Scheibe, Renate; Selinski, Jennifer; Zhang, Li-Tao; Yang, Cheng; Meng, Xiang-Long; Gao, Hui-Yuan (Molecular plant, 2017)
The mechanism by which the mitochondrial alternative oxidase （AOX） pathway contributes to photosystem II （PSII） photoprotection is in dispute. It was generally thought that the AOX pathway protects photosystems by dissipating excess reducing equivalents exported from chloroplasts through the malate/oxaloacetate （Mal/OAA） shuttle and thus preventing the over-reduction of chloroplasts. In this study, using the aoxla Arabidopsis mutant and nine other C3 and C4 plant species, we revealed an additional action model of the AOX pathway in PSII photoprotection. Although the AOX pathway contributes to PSII photoprotection in C3 leaves treated with high light, this contribution was observed to disappear when photorespiration was suppressed. Disruption or inhibition of the AOX pathway significantly decreased the photorespiration in C3 leaves. Moreover, the AOX pathway did not respond to high light and contributed little to PSII photoprotection in C4 leaves possessing a highly active Mal/OAA shuttle but with little photorespiration. These results demonstrate that the AOX pathway contributes to PSII photoprotection in C3 plants by maintaining photo- respiration to detoxify glycolate and via the indirect export of excess reducing equivalents from chloro-plasts by the MaI/OAA shuttle. This new action model explains why the AOX pathway does not contribute to PSII photoprotection in C4 plants.